Pengaruh Produk, Harga, Distribusi dan Promosi Terhadap Keputusan Pembelian - Arifin Arifin; Mutinda Teguh Widayanto; Hermanto Hermanto (Ecobuss, 2017)
This research was conducted on UD Furniture. Nur Agung Village of Muneng Kidul Sumberasih Subdistrict Probolinggo with the aim of research that will be achieved is a) to know the significant influence between product, price, distribution, and promotion simultaneously and partially to purchasing decision on UD furniture. Nur Agung Village Muneng Kidul District Sumberasih Probolinggo District. b) to know the variables among product, price, distribution, and promotion that have dominant influence to purchasing decision on UD furniture. Nur Agung Village Muneng Kidul District Sumberasih Probolinggo District. Type of research used is Quantitative research type with the associative approach, with variables used, include product, price, distribution, promotion, and purchasing decision. The sample used is 63 respondents. The results showed that there is significant influence between product, price, distribution, and promotion simultaneously to purchase decision on UD furniture. Nur Agung Village of Muneng Kidul Sumberasih Sub District Probolinggo, proved by a value of Fhitung (8,544)> Ftabel (2,530) and sig. = 0,000a <0.05. There is influence between product, price, distribution, and promotion partially to purchase decision seen result variable X1 count (3,656)> table (2,002) with sig value. = 0.001. Variable X2 count (2,605)> table (2,002) and sig value. = 0.012. Variable X3 count (2,884)> table (2,002) and sig value. = 0.006. Variable X4 count (3,006)> table (2,002) and sig value. = 0.004. The independent variable that has the most dominant influence on the dependent variable by seeing the largest significant t value is the product variable (X1) of 3,656 with a sig. 0.001 which influenced dominantly to variable Y from product variable (X2), distribution variable (X3) and promotion (X4). Keywords: product, price, distribution, promotion, and purchasing decision.